Study of performance of portfolio investment between industrial and financial sector / Siti Hawa Anuar - Anuar, Siti Hawa (2011)
The purpose of this study is to analyze the performance of the portfolio investment between two sectors which are industrial and hotel sector. This paper wills concentrated on the 3 companies for each sector that are listed in Bursa Malaysia Main Board. This study uses monthly stock price of each sectors over the period 2005 to 2009 that also included the market capitalization. The study will be tested using Markowitz theories which measure the performance with Sharpe performance measurement, Treynor performance measurement and Jensen performance measurement. The t-test is used to test the hypothesis in the different market size for both sectors. Diversification in industry and variation in market capitalization are two important factors considered in selecting the sample stock listed.